Non-pulverization pellet for treating zinc-containing dust through rotary hearth furnace and preparation method of non-pulverization pellet
By adding calcium and reducing agent to the zinc-containing dust pellets treated in the rotary bottom furnace to form a calcium ferrite phase, the problems of pulverization and insufficient strength of traditional pellets are solved, and pellet preparation with high strength and stability is achieved.
Patent Information
- Application Number
- CN202411725503.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Traditional rotary furnaces treat metallized pellets containing zinc dust often have severe pulverization, resulting in low mechanical strength and difficult to use in steel plants.
By adding an appropriate amount of calcium and reducing agent to the pellet, a small part of iron oxide is separated and calcium is combined, and a certain amount of calcium ferrite phase is formed after calcination, thereby improving the bonding strength of the pellet.
It effectively overcomes the problem of pulverization of traditional metallized pellets, improves the mechanical strength and structural stability of the pellets, reduces the pulverization phenomenon, and promotes the stability and durability of the pellets in the subsequent processing process.
Smart Images

Figure CN119614860A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of zinc-containing dust treatment, and particularly relates to a non-powdering pellet for treating zinc-containing dust in a rotary hearth furnace and a preparation method thereof. Background Art
[0002] As a pillar industry of the national economy, steel plays an irreplaceable role in promoting social infrastructure construction, energy development, and manufacturing industry upgrades. A large amount of industrial dust is inevitably generated in the steel production process, and zinc dust is one of them. Zinc dust not only has a large output and high iron content, but also contains elements such as zinc, potassium, and sodium. Although these dust sludges are recyclable secondary resources, due to their characteristics, they are usually difficult to reuse directly inside steel mills, resulting in a large amount of dust accumulation, posing a serious threat to the environment. Therefore, a reasonable method for treating zinc dust is of great significance to promoting the sustainable development of China's steel industry.
[0003] As the main process for treating zinc-containing dust, the rotary hearth furnace (RHF) technology has been widely used in the steel industry in recent years. This technology has the characteristics of large-scale treatment and high efficiency, and is particularly suitable for the resource utilization of zinc-containing dust. The process involves uniformly mixing the dust raw materials, reducing agents and binders to form green balls with a certain drop strength, and then the green balls are dried and sent to the rotary hearth furnace for reduction roasting. In the rotary hearth furnace, iron oxides are gradually reduced to metallic iron to form metallized pellets. However, these metallized pellets are often accompanied by severe pulverization, resulting in low mechanical strength, so they are usually not adopted by steel mills.
[0004] It is worth noting that the current research on the reduction and pulverization problem of metallized pellets produced after roasting zinc-containing dust pellets in a rotary hearth furnace is relatively limited. For example, the Chinese patent with publication number CN110788113A published on February 14, 2020 discloses a method for inhibiting the reduction and pulverization of zinc-containing dust pellets in a rotary hearth furnace. This method is particularly aimed at the production process of a rotary hearth furnace with a cloth thickness of two to three layers of pellets. The pellets with added composite additives are placed in the lower layer of the rotary hearth furnace, and the pellets without added composite additives are placed in the upper layer, so as to improve production efficiency and reduce the pulverization rate of metallized pellets. However, in the actual production of rotary hearth furnaces, many manufacturers at home and abroad still encounter pulverization problems when only one layer of pellets is laid for production, and the strength of the metallized pellets has not been significantly improved, which means that the application of zinc-containing dust pellets processed by rotary hearth furnaces is still difficult. The Chinese patent with publication number CN118374676A published on July 23, 2024, discloses a method for reducing the pulverization of metallized pellets in a rotary hearth furnace. The method performs special treatment on the process of mixing raw materials to prepare pellets before the rotary hearth furnace, and uses a powerful mixer to improve the internal mixing degree of the pellets. After the pellets are reduced and roasted in the rotary hearth furnace, the local unmixed sludge particles or carbon concentration inside the metallized pellets are significantly reduced, the internal mixing degree of the metallized pellets is good, the iron crystallization degree is high and evenly distributed, the pellet strength is increased, and the reduction pulverization rate of the metallized pellets is effectively reduced. However, this method still does not essentially change the problem of insufficient strength and easy pulverization of the pellets after roasting in the rotary hearth furnace. Summary of the invention
[0005] The purpose of the present invention is to provide a non-powdering pellet for treating zinc dust in a rotary hearth furnace and a preparation method thereof. The pellets prepared by adding an appropriate amount of calcium and a reducing agent separate a small amount of iron oxide and combine with calcium, and a certain amount of calcium ferrite phase is formed after roasting, so that the pellets are bonded into high-strength pellets to overcome the problem of powdering of traditional metallized pellets. The dry balls before roasting are improved, which lead to poor strength, cracking or powdering due to the introduction of calcium.
[0006] The specific technical solutions of the present invention are as follows:
[0007] The present invention provides a rotary hearth furnace for treating zinc dust-containing non-powdered pellets, comprising the following raw materials in parts by weight:
[0008] Reducing agent: 7%-10%,
[0009] Mixed binder: 1.8%-4%,
[0010] Zinc dust: 63%-72%,
[0011] Slaked lime: 6%-13%,
[0012] Water: 10%-15%;
[0013] The total amount of the above raw materials is 100%.
[0014] The reducing agent is coal powder;
[0015] The mixed adhesive comprises the following raw materials in percentage by mass: 75%-80% phenolic resin and 20%-25% epoxy resin;
[0016] The phenolic resin is a thermosetting phenolic resin JYPF2123C produced by Jiayuan New Materials Co., Ltd.
[0017] The epoxy resin is E51 produced by Tianjin Zhonglian Chemical Reagent Co., Ltd.
[0018] The zinc-containing dust is blast furnace, converter or electric furnace dust, with a dust particle size of <0.1 mm and a moisture content of <6%;
[0019] The slaked lime is calcium hydroxide;
[0020] The present invention provides a method for preparing non-powdered pellets containing zinc dust by treating the zinc dust in a rotary hearth furnace, comprising the following steps:
[0021] 1) Dry the ingredients except water in the formula and then mix with the water in the formula;
[0022] 2) The mixed material obtained in step 1) is pressed into balls, dried, and sent to a rotary hearth furnace for roasting under a protective atmosphere to obtain the product.
[0023] In step 1), the drying refers to drying to a moisture content of less than 2%;
[0024] In step 2), the pellets are pressed into raw balls of 10 to 40 mm using a high-pressure pellet press;
[0025] In step 2), the drying process is to dry the green balls into dry balls in a drying machine at a temperature of 105° C. for 6 hours;
[0026] In step 2), the rotary hearth furnace uses coke oven gas as fuel; the protective atmosphere is nitrogen atmosphere;
[0027] In step 2), the calcination is carried out by heating to a temperature of 1200° C. and keeping the temperature for 25-35 minutes, during which nitrogen is fully introduced, and then the temperature is lowered along with the furnace.
[0028] The invention provides an application of a rotary hearth furnace to process non-pulverized pellets containing zinc dust, which is used as an additive in sintering and converter processes, or as a raw material for negative expansion materials and photocatalytic materials, thereby achieving secondary utilization.
[0029] The inventors found that in the process of preparing carbon-containing pellets, the basic principle is to add an appropriate amount of carbon source to the raw pellets to achieve effective reduction of iron and zinc oxides. However, in the actual carbon reduction process, in order to ensure that the oxides can reach a relatively high degree of reduction, it is often necessary to add excessive carbon. This excess carbon is not completely consumed in the subsequent reaction process, and the residual carbon and other oxides are irregularly distributed in the pellets, resulting in the failure of the iron phase after reduction to be linked together, and then the strength of the pellets is poor and pulverization occurs, which has an adverse effect on the subsequent processing and utilization of the pellets after roasting. The present invention proposes a pellet prepared by adding an appropriate amount of calcium (slaked lime) and a reducing agent (coal powder), separating a small amount of iron oxide and combining with calcium, forming a certain amount of calcium ferrite phase after roasting, and bonding the pellets into high-strength pellets, overcoming the problem of pulverization of traditional metallized pellets. At the same time, it solves the problem of poor strength of dry balls before roasting due to the introduction of calcium under high calcium conditions, because the introduction of a large amount of calcium will change the microstructure of the pellets, weaken the bonding force of the pellets during the forming and drying stages, resulting in a decrease in strength and easy cracking or pulverization of the pellets.
[0030] The pellets of the present invention have excellent anti-pulverization performance. By introducing the calcium ferrite phase during the preparation process, the common pulverization phenomenon during high-temperature roasting is effectively avoided. The formation of the calcium ferrite phase not only enhances the structural stability of the pellets, but also significantly reduces the decomposition and pulverization tendency of the material during high-temperature roasting. This improvement greatly improves the stability and durability of the pellets in the subsequent processing process, reduces the material loss and environmental pollution caused by pulverization, thereby improving the economy and environmental protection of the entire production process. And the pellets prepared by the present invention have higher mechanical strength. This means that the pellets are not easy to break or deform when subjected to external forces, and can maintain a good physical form even during transportation and storage. The higher strength ensures the integrity and reliability of the pellets under various working conditions, especially in the secondary utilization process, can effectively resist external stresses such as extrusion and impact, and ensure that the pellets can still maintain good performance when they are recycled.
[0031] Compared with the prior art, the present invention realizes the preparation of non-powdered pellets and pellets with excellent performance under high calcium content. By optimizing the formula and process, the strength of the pellets is improved, and the damage during transportation and application is prevented, which greatly facilitates logistics and practical applications. The present invention not only solves the problem that traditional pellets are easy to pulverize during high-temperature roasting by introducing calcium ferrite phase, but also greatly improves the mechanical strength of the pellets, making them perform better in practical applications. This invention progress provides a new solution for the resource utilization of zinc-containing dust. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 The pellets are those in Comparative Example 1 without the addition of slaked lime;
[0033] Figure 2 The pellets after calcination in Example 1 do not show any pulverization phenomenon;
[0034] Figure 3 The pellets after calcination in Example 2 do not show any pulverization phenomenon;
[0035] Figure 4 The pellets after roasting in Comparative Example 3;
[0036] Figure 5 The pellet strength comparison of Example 3 and Comparative Examples 4-6;
[0037] Figure 6 The pellet strength comparison of Comparative Example 7, Comparative Example 8, Example 2 and Example 3;
[0038] Figure 7 The pellet strength comparison of Comparative Example 9, Comparative Example 10, Example 2 and Example 4 is shown. DETAILED DESCRIPTION
[0039] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0040] Unless otherwise specified, the test materials and reagents used in the following examples can be obtained from commercial sources.
[0041] If no specific techniques or conditions are specified in the examples, they can be carried out according to the techniques or conditions described in the literature in the art or according to the product instructions.
[0042] The cement used in the present invention is ordinary Portland cement (P·O);
[0043] The bentonite used was calcium-based bentonite from Tianjin Zhonglian Chemical Reagent Co., Ltd.;
[0044] The phenolic resin is a thermosetting phenolic resin JYPF2123C produced by Jiayuan New Materials Co., Ltd.
[0045] The epoxy resin is E51 produced by Tianjin Zhonglian Chemical Reagent Co., Ltd.
[0046] The starch used is soluble starch 10021318 produced by Sinopharm Chemical Reagent Co., Ltd.
[0047] Comparative Example 1
[0048] A method for preparing non-powdered pellets containing zinc dust by treating a rotary hearth furnace, specifically: the raw material composition of this comparative example is: Zinc dust electric furnace ash 75.51%, slaked lime 0%, reducing agent coal powder 12.49%, A mixed binder of 2% and water of 10%, wherein the mixed binder is composed of 25% epoxy resin and 75% phenolic resin; the particle size of the reducing agent, slaked lime and zinc-containing dust is less than 35 mesh (<0.5mm), the mixture is sent to a high-pressure ball press to be pressed into elliptical raw balls with semi-axes of about 10mm, 15mm and 10mm, and subjected to a pressure of about 40Mpa (the raw balls of other embodiments and comparative examples are also prepared according to the same size and method), and the raw balls are dried into dry balls in a dryer again, the drying temperature is 105°C, the drying time is 6h, and then sent to a rotary hearth furnace, the fuel used by the rotary hearth furnace is coke oven gas, and the nitrogen atmosphere is protected. The temperature in the rotary hearth furnace is heated to 1200°C, the insulation time is 30 minutes, nitrogen is introduced during the insulation period to ensure the reducing atmosphere, and then the temperature is lowered with the furnace.
[0049] This comparative example 1 does not add slaked lime, which is equivalent to the traditional carbon-containing pellets. The pellets after roasting showed extremely poor performance after testing, and the powdering phenomenon was particularly serious, such as Figure 1 As shown, secondary utilization is impossible.
[0050] Example 1
[0051] A method for preparing non-powdered pellets containing zinc dust by treating the zinc dust in a rotary hearth furnace comprises the following steps:
[0052] 1) Drying and mixing:
[0053] Raw materials were prepared by mixing the reducing agent pulverized coal, electric furnace ash, slaked lime, and mixed binder (the mixed binder consisted of 25% epoxy resin and 75% phenolic resin) in the proportions shown in Table 1. Blast furnace and electric furnace dust was used for zinc-containing dust, with a dust particle size of <0.1 mm and a moisture content of <6%. The moisture content of each raw material was reduced to less than 2% by a dryer, and then mixed evenly according to the proportions shown in Table 1.
[0054] 2) Ball pressing and roasting
[0055] The mixture is sent to a high-pressure ball press to be pressed into green balls, and then passed through a dryer to be dried into dry balls at a temperature of 105°C for 6 hours. The mixture is then sent to a rotary hearth furnace, which uses coke oven gas as fuel and is protected by a nitrogen atmosphere. The mixture is heated to 1200°C in the rotary hearth furnace and kept warm for 30 minutes. During the warm-keeping period, nitrogen is fully introduced, and then the mixture is cooled with the furnace to obtain the product.
[0056] 3) After the pellets are processed in the rotary hearth furnace and cooled to room temperature, they can be taken out of the furnace. Due to their high strength, these pellets can be used not only as additives in sintering and converter processes, but also as raw materials for negative expansion materials and photocatalytic materials, thus achieving secondary utilization.
[0057] Example 2
[0058] A method for preparing non-powdered pellets containing zinc dust by using a rotary hearth furnace comprises the following steps: the method is carried out according to Example 1, except that the raw material ratio is different, and the ingredients are prepared according to Table 1.
[0059] Comparative Example 2-Comparative Example 3
[0060] A method for preparing non-powdered pellets containing zinc dust by using a rotary hearth furnace comprises the following steps: the method is carried out according to Example 1, except that the raw material ratio is different, and the ingredients are prepared according to Table 1.
[0061] Table 1: Formulas of zinc dust-free balls of Comparative Examples 1-3 and Examples 1-2
[0062]
[0063]
[0064] The zinc dust-free balls of Comparative Examples 1 to 3 and Examples 1 and 2 were tested, and the results are shown in Table 2.
[0065] Test method:
[0066] 1. Strength compression pellets: Place the pellet sample to be tested between two parallel plates of the compression strength tester, and apply axial pressure to the pellet at a constant speed of 1-2mm / min until the pellet breaks. Record the maximum pressure value when the pellet breaks, which is the compressive strength of the pellet.
[0067] 2. Pulverization rate: Put the pellet sample to be tested into a standard drum and set the speed to 20 rpm. The drum rotates for 10 minutes. After the drum stops, sieve the material in the drum using a standard sieve with an aperture of 6.3 mm. The percentage of the mass of the sieved material to the total mass of the original pellet sample is the pulverization rate.
[0068] 3. Pellet drop strength: Drop the pellet sample to be tested at a height of 0.5m in a free fall manner, record the last drop number after breaking, and conduct multiple experiments. After removing the maximum and minimum values, take the average value.
[0069] Table 2 Performance test of zinc dust-free balls of comparative examples 1-3 and embodiments 1-2
[0070]
[0071]
[0072] According to Table 2, the powdering phenomenon of Comparative Example 2 is still very serious after roasting, because the amount of slaked lime added is too small, and it is almost the same as the traditional carbon-containing pellets. Therefore, the roasted pellets show extremely poor performance and cannot be reused.
[0073] The pellets after calcination in Example 1 did not show any pulverization phenomenon (such as Figure 2 After a series of rigorous tests, the results showed that the pellets have excellent performance, with an average compressive strength of more than 1700N, and can be fully reused.
[0074] Example 2 is similar to Example 1 (eg Figure 3 After roasting, the pellets have excellent performance and improved strength, and can be fully reused.
[0075] In Comparative Example 3, too much slaked lime was added. The performance of the pellets after roasting was excellent, and the strength exceeded 3000N. However, the pellets after roasting could not be fully formed (e.g. Figure 4 Therefore, it affects the subsequent reuse and is not the best choice.
[0076] Example 3
[0077] A method for preparing non-powdered pellets by treating zinc-containing dust in a rotary hearth furnace comprises the following steps: the raw material composition of the present embodiment is: 8.00% of reducing agent coal powder, 66.14% of zinc-containing dust in an electric furnace, 11.86% of slaked lime, 4% of a mixed binder (the mixed binder is composed of 25% of epoxy resin and 75% of phenolic resin), 10% of water, the particle size of the reducing agent, slaked lime and zinc-containing dust is less than 35 mesh (<0.5mm), 20g of the mixed raw materials are taken, and pellets are pressed with a pellet pressing mold at a pressure of 40Mpa for a holding time of 1min, the pellets are dried at a temperature of 105°C for 6 hours, and then strength tests are performed.
[0078] according to Figure 5 It can be seen that the pellets with mixed binder have excellent strength, with an average drop of 10 times and a compressive strength of more than 483N.
[0079] Comparative Example 4
[0080] A method for preparing non-powdered pellets by treating zinc-containing dust in a rotary hearth furnace comprises the following steps: the raw material composition of this comparative example is: 8.00% of reducing agent coal powder, 66.14% of zinc-containing dust in an electric furnace, and 11.86% of slaked lime, Add 4% bentonite, Moisture content: 10%; the particle size of the reducing agent, slaked lime and zinc-containing dust is less than 35 mesh (<0.5mm). Take 20g of the mixed raw materials and press them into balls using a ball press grinder. The pressure is 40Mpa and the holding time is 1min. The balls are dried at 105℃ for 6 hours and then the strength test is carried out.
[0081] according to Figure 5 It can be seen that the strength of the pellets made of bentonite is very unsatisfactory, with an average drop of 0.33 times and a compressive strength of 324N.
[0082] Comparative Example 5
[0083] A method for preparing non-powdered pellets by treating zinc-containing dust in a rotary hearth furnace comprises the following steps: the raw material composition of this comparative example is: 8.00% of reducing agent coal powder, 66.14% of zinc-containing dust in an electric furnace, and 11.86% of slaked lime, Add 4% cement, The moisture content is 10%, and the particle size of the reducing agent, slaked lime and zinc-containing dust are all less than 35 mesh (0.5mm). Take 20g of the mixed raw materials and press them into balls using a ball pressing grinder. The pressure is 40Mpa and the holding time is 1min. The balls are dried at 105℃ for 6 hours and then the strength is tested.
[0084] according to Figure 5 It can be seen that the strength of the pellets using cement as the binder is still not up to standard, with an average drop of 2 times and a compressive strength of 305N.
[0085] Comparative Example 6
[0086] A method for preparing non-powdered pellets by treating zinc-containing dust in a rotary hearth furnace comprises the following steps: the raw material composition of this comparative example is: 8.00% of reducing agent coal powder, 66.14% of zinc-containing dust in an electric furnace, and 11.86% of slaked lime, Add 4% starch , moisture 10%, the particle size of the reducing agent, slaked lime and zinc-containing dust are all less than 35 mesh <0.5mm), take 20g of the mixed raw materials, press them into balls with a ball pressing grinder, the pressure is 40Mpa, the holding time is 1min, the balls are dried at 105℃ for 6 hours, and then the strength test is carried out.
[0087] according to Figure 5 It can be seen that the strength of the pellets using starch as the binder does not meet the standard, with an average of 2.7 drops and a compressive strength of 283N.
[0088] Example 4
[0089] A method for preparing non-powdered pellets containing zinc dust by treating zinc dust in a rotary hearth furnace is prepared in the same manner as in Example 2, except that the raw material formula is in accordance with the proportions in Table 3.
[0090] Comparative Example 7-Comparative Example 10
[0091] A method for preparing non-powdered pellets containing zinc dust treated by a rotary hearth furnace is prepared in the same manner as in Comparative Example 6, except that the raw material formula is in accordance with the proportions in Table 3.
[0092] The dry balls prepared in Examples 2-4 and Comparative Examples 7-10 before calcination were tested according to the same compressive strength measurement method as described above. The results are shown in Table 3.
[0093] Table 3 Pellet raw material formula and dry ball performance test of Examples 2-4 and Comparative Examples 7-10
[0094]
[0095]
[0096] Comparative Example 7, Comparative Example 8, Example 2 and Example 3 constitute a set of parallel control experiments to investigate the effect of the amount of mixed binder added on the pellet performance. Figure 6 The data show that with the increase of the mixed binder amount, the performance of the pellets has been significantly improved. In particular, the pellet performance of Example 3 shows significant superiority, indicating that the appropriate amount of mixed binder added can significantly improve the comprehensive performance of the pellets.
[0097] Comparative Example 9, Comparative Example 10, Example 2 and Example 4 are a group of control experiments under different moisture conditions. Figure 7 According to the data analysis, as the moisture content increases, the performance of the pellets is significantly improved. In particular, Example 4 shows a good pellet performance. This result shows that an appropriate amount of moisture can promote the formation of pellets and improve their physical properties.
[0098] In summary, through the analysis of the results of the control experiment, the pellets of Example 1 and Example 2 showed excellent strength performance after calcination. In the dry ball performance test before calcination, Example 2, Example 3 and Example 4 respectively showed excellent pellet performance under different variable conditions, but excessive addition of binder will cause higher costs. For this reason, Example 4 should be the optimal condition. Example 4 has the same raw material ratio as Example 2 except for water and binder. High-temperature calcination will cause the binder and water to pyrolyze and volatilize, and the pellets presented are still the same non-powdered pellets as Example 2. Therefore, Example 4 is the best raw material ratio in the entire patent invention.
[0099] In order to ensure that the pellets after roasting are free of pulverization, on this basis, the pellets before roasting are guaranteed to have a certain strength, and the pellets are complete when entering the rotary hearth furnace. The present invention achieves high strength of the pellets and breaks through the pulverization of the pellets by manufacturing new pellets and introducing calcium ferrite phase. The core of the pellets is to maintain the integrity of the pellets and ensure that the pellets have sufficient strength. Secondly, by optimizing the binder formula, it is ensured that the pellets have sufficient bonding force during the molding process, thereby maintaining good structural stability during the subsequent processing process.
[0100] The underlined data above do not meet the requirements of the present invention.
[0101] The description of the above embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the protection scope of the present invention.
Claims
1. A rotary hearth furnace for treating zinc dust-free pellets, characterized in that: The rotary hearth furnace for treating zinc dust-free pellets comprises the following raw materials in parts by weight: Reducing agent: 7%-10%, Mixed binder: 1.8%-4%, Zinc dust: 63%-72%, Slaked lime: 6%-13%, Water: 10%-15%; The total amount of the above raw materials is 100%.
2. The method for treating zinc dust-free pellets in a rotary hearth furnace according to claim 1, characterized in that: The reducing agent is coal powder.
3. The method for treating zinc dust-free pellets in a rotary hearth furnace according to claim 1, characterized in that: The mixed adhesive comprises the following raw materials in percentage by weight: 75%-80% phenolic resin and 20%-25% epoxy resin.
4. The method for treating zinc dust-free pellets in a rotary hearth furnace according to claim 1, characterized in that: The zinc-containing dust is blast furnace, converter or electric furnace dust, with a dust particle size of less than 0.1 mm and a moisture content of less than 6%.
5. A method for preparing non-powdered pellets containing zinc dust by treating the zinc dust in a rotary hearth furnace according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: 1) Dry the ingredients except water in the formula and then mix with the water in the formula; 2) The mixed material obtained in step 1) is pressed into balls, dried, and sent to a rotary hearth furnace for roasting under a protective atmosphere to obtain the product.
6. The preparation method according to claim 5, characterized in that: In step 1), the drying refers to drying the raw materials until the moisture content is less than 2%.
7. The preparation method according to claim 5, characterized in that: In step 2), the ball pressing is performed into raw balls of 10 to 40 mm.
8. The preparation method according to claim 5, characterized in that: In step 2), the fuel used in the rotary hearth furnace is coke oven gas; and the protective atmosphere is nitrogen atmosphere.
9. The preparation method according to claim 5, characterized in that: In step 2), the calcination is carried out by heating the mixture to a temperature of 1200° C. and keeping the temperature for 25-35 minutes.
Citation Information
Patent Citations
Method for inhibiting reduction degradation of zinc-containing dust pellets in rotary hearth furnace
CN110788113A
Method for reducing pulverization of metallized pellets of rotary hearth furnace
CN118374676A
Production method of fluxed composite carbon-containing pellets used in blast furnace
CN104975173A
Method for recycling zinc, indium, iron and gallium from iron vanadium slag
CN107254585A
Reduction dezincification method for zinc-containing dust
CN110317950A